A feasibility study to assess the individual and combined effects of financial incentives and monetary contingency contracts on physical activity. (September 2019) - Budworth, Luke; Prestwich, Andrew; Sykes-Muskett, Bianca; Khatun, Khaledha; Ireland, James; Clancy, Faye; Conner, Mark
Abstract: Objectives: To assess the feasibility, and demonstrate the preliminary relative efficacy of, individual and/or combined financial incentives interventions for physical activity. Design: Eighty participants were randomised to conditions receiving either: (i) a monetary contingency contract (where individuals deposit money, forfeited or returned depending on goal achievement) plus a standard financial incentive (simple reward upon achievement), (ii) a monetary contingency contract only, (iii) a standard incentive only, or controls groups (iv) with or (v) without a set behavioural goal. Feasibility was investigated through assessment of intervention acceptability, cost-effectiveness, study retention, contamination and missing data. The effects of the interventions on (i) physical activity (daily steps over 2-weeks) and (ii) potential mediators (e.g. intentions) were assessed also. Results: Indicators of feasibility were generally positive, with high acceptability ratings, low drop-out and low missing data. Participants receiving monetary contingency contracts plus standard financial incentives had (i) increased steps above controls (with some evidence of superiority over monetary contingency contract-only participants), (ii) the highest prevalence of goal achievement and cost-effectiveness (being between 57 and 317% cheaper per goal achiever versus other conditions) and (iii) larger deposits than contingency contract-only participants (with some evidence that higher deposits increased steps). There was evidence of contamination between participants, but the results were mostly robust after excluding 'contaminated' participants. No differences were observed on psychological mediators. Conclusion: This feasibility trial found promising results for a combined strategy approach to physical activity incentivisation, though a larger confirmatory trial is required. Highlights: Of 5 approaches, combining loss and gain-framed monetary rewards most raised steps. Combining loss and gain-framed monetary rewards (vs. loss-framed) increased deposits. Larger deposits led to higher step counts. Interventions were rated as equally acceptable.